Pelvic Radiotherapy in Rectal Cancer Patients With Synchronous Potentially Treatable Liver Metastases - Yayu Huang; Genwen Chen; Xian Zhang; Yang Qian; Jian Wang (Cancer Reports)
ABSTRACT Background The optimal management strategy for Stage IV rectal cancer with potentially treatable liver metastases remains controversial, particularly regarding the role of pelvic radiotherapy (RT). Aims We intend to investigate the impact of pelvic RT on oncological outcomes of rectal cancer with potentially treatable liver metastasis. Methods and Results This retrospective study included 83 patients diagnosed with rectal cancer and synchronous liver metastases from June 2012 to January 2022. All patients underwent radical surgery for rectal cancer and treatment of synchronous liver metastases, as determined by a multidisciplinary team (MDT). We divided the 83 patients into two treatment groups: chemoradiotherapy and surgery (CRT + S) and chemotherapy and surgery (C + S). The CRT + S group (n = 40) received pelvic RT, systemic therapy, and liver metastasis treatment. The C + S group (n = 43) received systemic therapy and liver metastasis treatment only. A total of 83 patients were analyzed with a median follow‐up of 45 months (range 12–127 months). In the CRT + S group, 48.2% (40/83) of patients underwent chemoradiotherapy, while the C + S group comprised 51.8% (43/83) of patients who received chemotherapy only. The CRT + S group demonstrated significantly longer local recurrence‐free survival compared to the C + S group (median 37.5 vs. 34 months; p = 0.011). In addition, patients in the CRT + S group had a longer median overall survival (OS) compared to the C + S group (46.50 vs. 44.0 months; p = 0.0497). Notably, achieving no evidence of disease (NED) status after definitive treatment for both primary and liver metastases was associated with improved OS (p = 0.008). Conclusion This study suggests that the addition of pelvic RT to multimodality therapy for patients with rectal cancer and potentially treatable liver metastases may improve local control and long‐term survival. The findings support the consideration of RT in the clinical management of this patient population.